2019
DOI: 10.1016/j.jsams.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of team and individual athlete performances on match quarter outcome in elite women’s Australian Rules football

Abstract: The relationship of team and individual athlete performances on match quarter outcome in elite women's Australian Rules football

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…By replicating the demands of matches, coaches may be able to better prepare their team for the congested nature of AFLW competition. The PIs that were identified as important here are similar to those identified by Cust et al (2019) who also found that kicks, inside 50s and contested possessions were important. Black et al (2019) also found that inside 50s were important, but in contrast to the present study, found that uncontested possessions were also important.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…By replicating the demands of matches, coaches may be able to better prepare their team for the congested nature of AFLW competition. The PIs that were identified as important here are similar to those identified by Cust et al (2019) who also found that kicks, inside 50s and contested possessions were important. Black et al (2019) also found that inside 50s were important, but in contrast to the present study, found that uncontested possessions were also important.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, kicks and contested marks were related to final ladder position. Cust et al (2019) explored the issue further by examining how the relative contribution of individual players to whole of team technical performance, was related to the outcome of a quarter in a match. Based on 13 technical PIs from two seasons of AFLW, they found that the contribution of high-performing players was more important than the collective team effort.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, work is required to determine the relationship between player positioning and match event outcomes that occur continuously throughout a match. Player positioning and performance outcomes can also be influenced by various contextual variables, such as, match phase, ball location, and quality of opposition [6][7][8]. Thus, contextual variables should be included when assessing how players occupy different sub-areas on a playing field and how this may influence player positioning and match event outcomes [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of evidence for contact skills and training behaviours, it can be postulated that contact skill coaching, frameworks and preparatory strategies in female field collision sports are underpinned by research and experiences in male populations. Applying contact skill evidence in male athletes to female athletes may be misguided considering the differences in locomotor and collision demands 2 , physiology 5 , selection and execution of technical skill 39 44 45 and team tactics 2 48 61 62 . The data provided in this review does not support the generalisation of male-derived training data to female field collision athletes.…”
Section: Discussionmentioning
confidence: 99%